Dialogue between centrosomal entrance and exit scaffold pathways regulates mitotic commitment - Chan, Kuan Yoow (J Cell Biol, 2017)
The fission yeast scaffold molecule Sid4 anchors the septum initiation network to the spindle pole body (SPB, centrosome equivalent) to control mitotic exit events. A second SPB-associated scaffold, Cut12, promotes SPB-associated Cdk1–cyclin B to drive mitotic commitment. Signals emanating from each scaffold have been assumed to operate independently to promote two distinct outcomes. We now find that signals from Sid4 contribute to the Cut12 mitotic commitment switch. Specifically, phosphorylation of Sid4 by NIMA(Fin1) reduces Sid4 affinity for its SPB anchor, Ppc89, while also enhancing Sid4’s affinity for casein kinase 1δ (CK1δ). The resulting phosphorylation of Sid4 by the newly docked CK1δ recruits Chk2(Cds1) to Sid4. Chk2(Cds1) then expels the Cdk1–cyclin B antagonistic phosphatase Flp1/Clp1 from the SPB. Flp1/Clp1 departure can then support mitotic commitment when Cdk1–cyclin B activation at the SPB is compromised by reduction of Cut12 function. Such integration of signals emanating from neighboring scaffolds shows how centrosomes/SPBs can integrate inputs from multiple pathways to control cell fate.